Application of 2D polymerase chain reaction for single-tube detection of high-risk human papillomaviruses - Wang, Weifeng; Jiang, Min; Liu, Ying; Wu, Xuan; Chen, Yan; Zhang, Xiaoyun; Liu, Weiwei (Frontiers in Microbiology, 2025)
PurposeThe persistent infection of high-risk HPV (HR-HPV) is intricately linked to the onset and progression of cervical cancer. This research endeavored to develop a high-throughput 2D PCR method for closed-tube genotyping of 11 HR-HPVs.MethodsBase-quenched probes were specifically designed for FAM, VIC, and CY5 channels. The 2D PCR system underwent optimization, with its detection performance assessed in terms of specificity and sensitivity. Plasmid mixtures was used to simulate multiple infections of HPV, providing preliminary insights into the detection efficacy and throughput of the 2D PCR technology. Ultimately, the detection capability of this method was assessed using clinical samples.ResultsThe sequenced tags, when paired with primers, could generate Tm differences exceeding 3°C. These were then integrated with a fluorescent channel and Tm to differentiate and identify target genes upon detection. The refined 2D PCR system was confirmed to be free from cross-reactions and exhibited high specificity, capable of detecting 12 target genes within a single tube. A total of 294 cervical exfoliated cell samples were tested using 2D PCR and flow fluorescence hybridization method. The overall concordance between the two detection methods was 96.17% (Kappa = 0.910).ConclusionThe 2D PCR method, which integrates asymmetric PCR amplification with melting curve analysis, has the capacity to detect 11 types of HR-HPVs across three channels. This closed-tube detection approach offers several benefits including high throughput, straightforward operation, and low detection cost. Consequently, it can be effectively utilized for early screening and prevention of cervical cancer.